Review of hybrid PLGA nanoparticles: Future of smart drug delivery and theranostics medicine - Jana Ghitman; Elena Iuliana Biru; Raluca Stan; Horia Iovu (Materials & Design, 2020)
The concept of PLGA-lipid hybrid nanoparticles arose as a motivation for developing drug delivery systems with versatile physical and chemical properties, unequivocal therapeutic benefits and minimized side effects. These formulations opened a new avenue of “smart tools” in the development of personalized, noninvasive emerging nanomedicine. However, there is still the risk that smart hybrid system manufactured from a mixture of materials, such as PLGA in combination with synthetic/vegetable lipids and targeting agents might trigger high nanotoxicological responses. This review is focused on the detailed description of PLGA-lipids/oils hybridization concept and its effect on the performances of nanocarriers as powerful, versatile delivery system, the manufacturing methods, the main applications, and their potential clinical impact. The successful design of a hybrid formulation involves two foremost challenges, firstly a comprehensive consideration of essential characteristics of each constituent that form the hybrid system and secondly, a deep understanding of the interactions of hybrid nanocarrier with cells in order to predict the potential toxicity issues and ensure its safe clinical applications.